Assessing chronic pain in the ankle and foot using Magnetic Resonance Imaging (MRI) - kast, Sunil; Chauhan, Ankit; kumar sharma, Yogesh; Khandekar, Ashwini (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Chronic ankle and foot pain is a common and non-specific manifestation of a broad spectrum of osseous and soft tissue pathology in the ankle and foot. MRI can play an important role in the diagnosis of these conditions and help to guide conservative management. Aim: The aim of this study was to assess the normal anatomy and anatomical variations, as well as to examine the MRI features that provide vital clues for the diagnosis of painful conditions of the ankle and foot. Another objective was to differentiate these conditions from one another using MRI imaging. Methodology: This was a descriptive study of 50 patients presenting with pain in the ankle and foot who underwent MRI examinations at the Department of Radiodiagnosis, Pacific Institute of Medical Sciences from November 2022 to February 2023. Results: The most common cause of chronic pain in the ankle and foot in our study was ligament pathology, which was found in 12 (24%) of the 50 patients. Tendon injuries were the next most common cause, present in 10 (20%) patients. Other causes included arthritis, bursitis, osteomyelitis, and ganglion cysts. The most affected age group was 21 to 30 years old. Conclusion: MRI is the modality of choice for the evaluation and characterization of various pathologies of the ankle. Most of the conditions can be managed conservatively. This study highlights the importance of MRI in the diagnosis and management of chronic ankle and foot pain.